A review of Phyllanthus urinaria L. in the treatment of liver disease: viral hepatitis, liver fibrosis/cirrhosis and hepatocellular carcinoma - Liu, Linhua; Wang, Bing; Ma, Yibo; Sun, Kunhui; Wang, Ping; Li, Meifang; Dong, Junlin; Qin, Meirong; Li, Mingshun; Wei, Chunshan; Tan, Ying; He, Jinsong; et al. (Frontiers in Pharmacology, 2024)
Due to the pathological production of liver disease in utility particularly complexity, the morbidity and mortality of liver disease including viral hepatitis, liver fibrosis/cirrhosis and hepatocellular carcinoma (HCC) are rapidly increasing worldwide. Considering its insidious onset, rapid progression and drug resistance, finding an effective therapy is particularly worthwhile. Phyllanthus urinaria L. (P. urinaria), an ethnic medicine, can be applied at the stages of viral hepatitis, liver fibrosis/cirrhosis and HCC, which demonstrates great potential in the treatment of liver disease. Currently, there are numerous reports on the application of P. urinaria in treating liver diseases, but a detailed analysis of its metabolites and a complete summary of its pharmacological mechanism are still scarce. In this review, the phytochemical metabolites and ethnopharmacological applications of P. urinaria are summarized. Briefly, P. urinaria mainly contains flavonoids, lignans, tannins, phenolic acids, terpenoids and other metabolites. The mechanisms of P. urinaria are mainly reflected in reducing surface antigen secretion and interfering with DNA polymerase synthesis for anti-viral hepatitis activity, reducing hepatic stellate cells activity, inflammation and oxidative stress for anti-liver fibrosis/cirrhosis activity, as well as preventing tumor proliferation, invasion and angiogenesis for anti-HCC activity via relevant signaling pathways. Accordingly, this review provides insights into the future application of natural products in the trilogy of liver diseases and will provide a scientific basis for further research and rational utilization of P. urinaria.